Medication Errors Made by Nursing Students in Turkey. - Gunes, Ulku; Efteli, Elcin; Ceylan, Burcu; Baran, Leyla; Huri, Ozturk (International Journal of Caring Sciences)
Background: Medication errors are a serious problem in the world and one of the most common medical errors that threaten patient safety. Current studies on medication errors focuses on nurses, there is insufficient data available concerning the type of medication errors committed by nursing students. Objectives: The purpose of this study is to determine the types of medication errors made by the nursing students through a web-based medication error reporting system, and to explore the causes of these errors, their frequencies, categories and the factors that contribute to their occurrence. Design: A descriptive study. Setting: A faculty of nursing in Turkey Participants: All 2nd, 3rd and 4th year nursing students (1156 students) in the faculty of nursing Methodology: The study was conducted in a faculty of nursing between the years of 2016 - 2017. We developed a web-based medication error reporting system for nursing students to use during their clinical practices. All students (1156 students) who were in clinical practice were invited to participate. The students used the "Medication Error Reporting System" to submit their medication errors. Results: A total of 1156 students reported 72 medication errors over the course of 28 weeks. The most common type of medication error to be reported was "treatment delay" at a rate of 76.4% and the most common cause of medication errors was "poor communication" at a rate of 38.7%. Conclusions: Although the reporting rate is quite low, we have suspected that the number of medication errors involved nursing students may be probably more than the reported. The medication errors made by nursing students are generally due to a lack of knowledge and experience, poor communication and carelessness. Therefore, patient safety issues should be integrated throughout the courses offered in the nursing program in order to develop the culture of safety.